The Impact of Corporate Governance Characteristics On Earnings Management In Palestine: The Moderating Effects Of Political Instability - Ali Hassan Ibraheem Aljadba (Universiti Sains Islam Malaysia, 2024)
4171048-Restricted until April 2024